KNOWLEDGE, ATTITUDE AND PRACTICE OF HEALTHCARE WORKERS TOWARDS NOVEL CORONA VIRUS (COVID-19) IN JUGAL HOSPITAL, HARARI REGIONAL STATE, ETHIOPIA - Jamie, Arif Hussen (YCAB Publisher & IAKMI SULTRA, 2020)
Introduction: Coronavirus (CoVs) belong to the subfamily Corona virinae in the family of Corona viridae of the order Nido virales, and this sub family includes four genera: Alpha corona virus, Beta corona virus, Gamma corona virus and Delta corona virus. The genome of CoVs is a single